What 80's pop culture teaches us about today's workplace : mix tape # 1 - Clews, Chris ([Florida] : Farmer Ted Publishing, 2019)
"From '80s pop culture expert Chris Clews comes another business book that defies the stereotypes - What '80s pop culture teaches us about today's workplace - Chris teaches us business professionals at all levels, in every industry and in diverse functional areas that there are fresh, fun ways to sharpen their skills in the workplace... Are '80s movies really imbued with timeless lessons for workplace? Yes! The era of parachute pants, Members Only jackets, padded shoulders and huge plastic earrings offers practical, timeless lessons for businesses of all kinds. See these movies through the eyes of marketing expert and keystone speaker Chris Clews, and you'll never see them the same way again."--Page 4 of cover.
1. Ferrris Bueller -- 2. The Goonies -- 3. Lloyd Dobler and say anything -- 4. Clark Griswold -- 5. Axel Foley and Beverly Hills cop -- 6. Back to the future -- 7. E.T. -- 8. Stand by me -- 9. Planes, trains and automobiles -- 10. The Breakfast club
Includes bibliographical references.
Keywords: MOTION PICTURES -- INFLUENCE